Avaliação da remoção orgânica e nitrogenada de reator anaeróbio-aeróbio de leito fixo para o tratamento de efluente bovino - Gatti, Raphael Augusto Ferreira (2013)
This study aimed to evaluate the performance of an Anaerobic - Aerobic Fixed -Bed (RAALF), operated in upflow with immobilized biomass for the treatment of raw wastewater from beef slaughterhouse in terms of removal of organic matter and nitrogen. The RAALF was operated with hydraulic retention time (HRT) of 22, 16 and 10 hours. The following physico-chemical parameters were evaluated: liquid temperature (LT) , dissolved oxygen (OD), pH , total Kjeldahl nitrogen (TKN) , ammonia nitrogen (Namon) ,nitrite, nitrate, phosphorus (P) , total solids (TS) , total suspended solids (TSS) , alkalinity to bicarbonate (AB) , volatile fatty acids (VFA) , chemical oxygen demand and crude filtered (COD) for each HRT tested . The samples were collected along the reactor height. The results indicated that the HRT of 22h showed better performance in the removal of organic matter in terms of COD gross efficiency of 98.0 % with and 16 HRTs for 10 hr, the efficiency was 95.0 % and 87.0%, respectively. Regarding filtered COD efficiencies were 95.0%, 94.0% and 83.0 % for 22 HRTs 16 and 10 hours respectively. As for the removal of nitrogenous matter in terms of TKN and Namon and the results showed efficiencies of 90.7 % and 96.0% respectively for the HRT of 22 hours. The HRT 16 h showed an efficiency of 95.0% and 94.0 % and HRT of 10 hours, said removal and TKN and Namon 80.0% and 93.0%, respectively. The concentration of nitrite and nitrate for 22 HRTs 16 and 10 hours was from 0.1 to 0.4 mg.L-1 and 4.6 to 57.8 mgN. L-1, 0.02 to 0, 3 mg.L-1 and from 4.9 to 35.0 mgN.L-1 and from 0.3 to 0.7 mg.L-1 and 51.7 to 80.0 mgN.L-1, respectively. The degradation kinetic model that best fitted the data of organic matter removal was first order , the values of kinetic constant of degradation ( k ) obtained were 0.133 h-1, 0.158 h-1 and 0.156 h-1 for the HRTs, 22, 16 and 10 h with r² of 0.9544 , 0.9211 and 0.7262 , respectively. As the kinetics of nitrogen removal , the degradation kinetics model best fit was zero order , which showed values of k equal to 4.6789 h-1, 9.7142 and 6.8275 h-1 for the TDHS , 22 , 16 and 10 h with r² 0.985 , 0.9345 and 0.9616 , respectively.